ANALISIS KONDISI TRANSFORMATOR DENGAN PENGUJIAN GAS TERLARUT PADA PT. PLN INDONESIA POWER GRATI PGU - Imtiyaz, Kholis; Wibawa, Unggul; Dhofir, Moch. (Jurnal Mahasiswa TEUB, 2024)
Abstract - Transformers have an important role in the transmission and distribution of electricity, therefore the reliability of the transformer must be maintained, especially the insulating oil, in the process the insulating oil will produce dissolved gases and this can be called fault gas, fault gas can be analyzed using DGA (Dissolved Gas Analysis) , so that it can show the diagnosis of the transformer. In the flow of this research method, first a literature study will be carried out from three main sources, namely : journals, scientific articles and e-books, especially related to dissolved gas or DGA (Dissolved Gas Analysis), then data will be taken from transformer 2.1 at PT. PLN Indonesia Power Grati PGU, where the data taken is related to the results of the DGA (Dissolved Gas Analysis) test, and the data will be analyzed using the Roger's Ratio and Duval Triangle methods The results of the influence of the long operating time have an impact on changes in several gases which have increased beyond the maximum limit, such as CO (Carbon Monoxide) and CO2 (Carbon Dioxide), and from the results of the analysis of the Roger' Ratio and Duval Triangle methods, it is known to have several different results, for the Roger' Ratio method has normal unit results, low temperature thermal, and low energy density arcing-pd and the Duval Triangle has partial discharge results, but in this test method there are also results that cannot be detected using the Duval Triangle method, these two methods have several differences related to the conditions of each method that have been tested using the same data, the differences in condition indications do not mean that one method is superior to another method, but the differences in condition indications strengthen the results of the previous method's indications so that the methods are used to reinforce each other because these methods also use different processing methods. Keywords —Transformer, Fault Gas, DGA (Dissolved Gas Analysis), Duval Triangle, Roger' Ratio